Basic and clinical science of opioid addiction - Kuntze, Marcus Frederic; Müller-Spahn, Franz 1950-2009; Ladewig, Dieter 1938-; Bullinger, Alex H. (Bibliotheca psychiatrica, 2003)
For the first time reports on methadone and heroin maintenance treatment with respect to clinical practice, research, methodological aspects, neuroscience and psychotherapy are brought together in this volume. They arise from a conference held in November 2001 in Basel. The Swiss approach of a highly structured outpatient treatment using methadone, heroin, morphine etc. to keep patients in treatment is discussed. Data of follow-up after heroin-assisted treatment is shown. Also a critical discussion of the history of treatment modalities and its scientific evaluation is presented. Further important topics such as brain imaging, opioid withdrawal, risks of treatment, and basic neurochemical research are presented. The issue concludes with the narrative experience of a practicing psychotherapist. This topical and outstanding overview gives psychiatrists, psychologists and psychotherapists, neuroscientists, physicians as well as decision makers in public health, politicians, counselors and social workers an excellent insight into stimulating and scientific research